A4_7 Supermassive (Interstellar) Black Hole - Sullivan, Claire; Sallabank, Jonathan; Foden, Alex; Higgins, Adam (Physics Special Topics, 2014)
This paper considers the plausibility of an event from the 2014 film Interstellar. It states that an hour on a planet orbiting a supermassive back hole is equivalent to 7 years passing on Earth. Calculations made state that the planet is inside the minimum orbit for a planet around a black hole and would thus fall with a ballistic trajectory into the centre.However, a static system was assumed, so with an optically spinning black hole the planet may be in a stable orbit. A spacecraft orbiting at a distance unaffected by time dilation is also considered and found to be largely implausible.